New Insight Into the Mechanism of Ecological Effects of Artificial Habitats: Elucidating the Relationship Between Protists Associated With Artificial Reefs and Adjacent Seawater - Li, Ruolin; Guo, Yu; Qin, Chuanxin; Zhang, Shuo; Ji, Dongping; Zhang, Hui; Wang, Jing; Zhao, Naiqian (Frontiers in Marine Science, 2022)
Artificial habitat deployment can restore natural habitats or supplement existing natural habitats. The effect of resource proliferation and protection is obvious. However, few reports have addressed the biological community association between artificial habitats and adjacent environments. Here, Illumina sequencing of 18S rDNA was performed, and the diversity, community structure, and co-occurrence networks of protists in different layers of artificial reefs (ARs) and adjacent seawater (WAR) were described to verify that constructing ARs in Bailong Pearl Bay improves local spatial heterogeneity and functional diversity. In terms of the degree of species interaction, the protist communities were ranked as follows: surface and bottom of WAR > ARs and WAR > different layers of ARs. The α-diversity of protists associated with ARs and WAR decreased with an increase in depth. Protist diversity was greater in WAR than in ARs. β-Diversity analysis revealed significant differences in protist community structure between WAR and ARs (P < 0.05), and the upper layers of ARs and the middle or bottom layers of ARs differed. The key topological features of protist networks showed more positive interspecific interactions in the AR-associated protist community, a higher degree of niche differentiation, and higher complexity and stability. The keystone protists in the bottom seawater layer displayed community functions that were biased toward initial fixation in the ocean carbon cycle. The AR-associated protist community tended to participate in carbon transfer in the food chain and decomposition and utilization of dissolved organic matter (DOM). This study revealed significant differences in protist community structure between ARs and the adjacent environment, and the ecological functions of the key phyla were found to be related. In conclusion, protist communities in WAR may provide food sources for AR-associated heterotrophic protists. A variety of key phyla associated with ARs have biological roles in the carbon pump via their ecological characteristics.